PEDAGOGICAL TERMS FOR THE ORGANIZATION OF THE INFORMATIONAL AND CONSULTING ENVIRONMENT OF THE EDUCATIONAL INSTITUTION: INNOVATIVE APPROACHES AND VECTORS OF DEVELOPMENT - Skripnik Lyudmyla (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2022)
The article fixes the fact that in view of the emphasis on the independent acquisition of knowledge by students, the consulting and corrective components of the pedagogues’ professional activity are strengthened. They have to carry it out in the institution’s information educational space and for this purpose possess by modern ICT and tools, both in the field of basic and related educational subjects. The aims of the article are to substantiate the pedagogical terms for the organization of an informational and consultative environment and to highlight the requirements for its productive functioning both for those seeking education and for the pedagogical staff, which will ultimately ensure high quality of educational services. Such methods as analysis, generalization, systematization, extrapolation and SWOT analysis were used to study indicators of the functioning of the informational and consultative environment of vocational education institutions in Ukraine; as well as modelling and substantiating the pedagogical terms for its optimal organization. A study of the state of the issues of the organization of the information and consultative environment in educational institutions in Ukraine has been carried out according to the functional-structural criterion. It covers such indicators characteristic of the subjects of the environment (internal and external) as immersiveness, presence, interactivity, saturation, structuredness, openness, scalability and adaptability. A SWOT analysis has been carried out, which made it possible to identify the advantages and risks, strengths and weaknesses that take place in the organization of the information and consultative environment of vocational education institutions. The conceptual, substantive, organizational and technical-technological difficulties in the organization of the informational and consulting environment of the educational institution have been clarified and summarized. The organizational, technical, methodical and resource conditions that collectively contribute to the organization of the informational and consultative environment of the educational institution have been identified and described. It has been substantiated that the combination of the above-mentioned factors makes it possible to formulate a set of necessary and sufficient pedagogical terms. Among them: the readiness of pedagogical staff and students for consultative activities with the use of modern ICT; resource provision of advisory activities focused on the content of professional education; implementation of multi-channel and multi-disciplinary online counselling, which realizes the functions of the educational institution information environment; creative and developmental subject-subject interaction via ICT and tools, which initiates methodological reflection of pedagogues and students in consultative activities. It was concluded that the creation of the specified pedagogical terms will enable the functioning of all components of the educational institution’s information and consultative environment in the best relationship, will ensure the creation of an atmosphere of fruitful cooperation, productive learning, effective management of the study process, as well as the provision of quality educational services. Prospects for further research are defined in the creation of a methodology for the organization of informational and consultative environments in a professional education institution and its empirical verification.